Baicalein attenuates impairment of hepatic lysosomal acidification induced by high fat diet via maintaining V-ATPase assembly. (February 2020) - Zhu, Xinhong; Yao, Ping; Liu, Jingjing; Guo, Xiaoping; Jiang, Chunjie; Tang, Yuhan
Abstract: Baicalein has been proved as a promising compound for non-alcoholic fatty liver disease (NAFLD); however, the molecular mechanisms underlying the progression of NAFLD and its intervention by baicalein remain largely obscure. Male C57BL/6J fed high-fat diet (HFD) and HepG2 cells stimulated with free fatty acid were treated with baicalein and various pharmacological reagents to explore the effect of signaling pathways involved in lysosomal acidification. Baicalein intake declined ALT and AST activities by 25.1% and 18.7%, respectively, compared with the HFD group. Moreover, baicalein markedly ameliorated the HFD-trigged lysosomal membrane permeabilization evidenced by declined cathepsin B release. Subsequent disorders, including cathepsin D maturation and mitochondrion membrane potential were also partially normalized by baicalein administration to HFD-fed mice. Meanwhile, an increase in V-ATPase V1 subunits expression in lysosomes, V-ATPase activity and the colocalization of cytosol V-ATPase V1 subunits and lysosomes was observed in baicalein-supplement mice. Bafilomycin A1 stimulation resulting in elevated lysosomal pH and triacylglycerol accumulation partially abolished the effect of baicalein. Furthermore, incubation with mTOR inhibitor rapamycin restored lysosomal pH and decreased cellular triacylglycerol content. Collectively, these findings demonstrate that hepatic lysosomal acidification is the main target of baicalein against NAFLD via maintaining lysosomal V-ATPase assembly through mTOR pathway. Highlights: Baicalein ameliorates LMP and MMP delivered by HFD. Baicalein restores lysosomal acidification via promoting V-ATPase assembly. The effect of baicalein on V-ATPase assembly is mediated by mTOR-dependent way.